2019
DOI: 10.1136/bmjopen-2019-029105
|View full text |Cite
|
Sign up to set email alerts
|

Changing conversations in primary care for patients living with chronic conditions: pilot and feasibility study of the ICAN Discussion Aid

Abstract: PurposeTo pilot test the impact of the ICAN Discussion Aid on clinical encounters.MethodsA pre–post study involving 11 clinicians and 100 patients was conducted at two primary care clinics within a single health system in the Midwest. The study examined clinicians’ perceptions about ICAN feasibility, patients’ and clinicians’ perceptions about encounter success, videographic differences in encounter topics, and medication adherence 6 months after an ICAN encounter.Results39/40 control encounters and 45/60 ICAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…All HCPs felt that their efforts to assist with burden and capacity were limited by contextual factors over which they had little power. Consistent with other literature [ 41 , 42 ], some experienced their own personal ‘treatment burden’ in trying to fill the gaps of poor service provision, and others stepped outside of their role to provide additional support or co-ordination if it was unavailable in their healthcare setting. They felt that many barriers could only be dealt with by the injection of more money and practical approaches including better technology, administrative support, stronger linkages between health and social services and time allocated for HCPs to communicate directly to each other.…”
Section: Discussionsupporting
confidence: 64%
“…All HCPs felt that their efforts to assist with burden and capacity were limited by contextual factors over which they had little power. Consistent with other literature [ 41 , 42 ], some experienced their own personal ‘treatment burden’ in trying to fill the gaps of poor service provision, and others stepped outside of their role to provide additional support or co-ordination if it was unavailable in their healthcare setting. They felt that many barriers could only be dealt with by the injection of more money and practical approaches including better technology, administrative support, stronger linkages between health and social services and time allocated for HCPs to communicate directly to each other.…”
Section: Discussionsupporting
confidence: 64%
“…There are interventions we have not included in Table 3 , but which have beneficial potential and are worthwhile areas for future research. First, in relation to the previously discussed high treatment burden upon many people with DCC, research has recently developed conversation aid tools to help clinicians assess and discuss treatment burden, and thus take actions to improve illness workloads for highly burdened patients [ 22 ]. Evidence for these tools is still in progress, but they may assist oncology staff in understanding an individual’s holistic ‘medical and social landscape’ and thus providing the individualised care needed by people with DCC.…”
Section: Discussionmentioning
confidence: 99%
“…Observations during clinical encounters and nurse home visits were followed by the development and testing prototypes, resulting in the final ICAN Discussion Aid (see Additional file 6 ). The ICAN was found feasible to use during clinical encounters [ 46 ]. Using videographic coding scheme, results also showed that issues discussed with the ICAN were seldom discussed during control clinical encounters [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ICAN was found feasible to use during clinical encounters [ 46 ]. Using videographic coding scheme, results also showed that issues discussed with the ICAN were seldom discussed during control clinical encounters [ 46 ]. A randomized controlled trial is ongoing to test the impact on patient and healthcare teams’ care experience and communication, while reducing patient treatment burden (NCT03017196).…”
Section: Methodsmentioning
confidence: 99%